Menerapkan Pola Regenerasi Kepemimpinan Musa kepada Yosua - Michael Salomo Hahuluy (Jurnal Teologi Gracia Deo, 2020)
This scientific work discusses, how can today's leaders understand the importance of regeneration of leadership. In this thesis will see various views associated with leadership and regeneration, which have an impact on issues of Theology and praxis related to problems of regeneration of leadership. Then from the various views, will be compared with the results of the study of regeneration of the historical leadership of Moses to Joshua, which is contained in the book of Pentateuch. The author gives some examples of patterns of regeneration. The results of this research are the leaders can understand the importance of leadership regeneration, as well as a biblical basis with regard to the regeneration of leadership. The leaders are expected to be: first, aware of the urgency of making the regeneration of leadership. Second, immediately perform the regeneration of leadership, to begin looking for the people who have competence in leadership, rig up to hand over the relay baton of leadership to the new leaders.